Desenvolvimento de uma ferramenta computacional para ensino da operação unitária de evaporação - Mateus Filho, Paulo Rubens (2021)
The job market demands that the engineer has knowledge of a diverse range of software and computer programs to solve problems that may occur in the daily life of the industry. It is extremely important that engineering students have contact to get used to the use of software during their training, learning its operation, developing new tools or using them to aid in learning operations that have complex or extensive mathematical modeling. The ability to use software can be a positive differential for the engineer. The assimilation of the process, the development of critical thinking and a greater perception of the effect of variables on the system are the main benefits that the use of software for teaching can offer. It is noteworthy that these tools are not intended to replace traditional teaching nor work as a result calculator. They seek to favor the cause and effect tests, performed through simulation with extrapolation of physical conditions in the model, increasing the perception of the effect of each variable in the response of the unit operation. With mastery of the equation, the student, in a short period of time, can perform several simulations, improving the understanding of the unit operation. A computational tool structured in Python was developed to teach the unitary evaporation operation. This tool allows you to solve exercises and compare processes that have up to five effects in an easy and intuitive way, with step-by-step graphics and resolutions to help the student's understanding of the equation of the operation. With the tests carried out in this work, it can be seen that the developed tool can be very effective and can be used by engineering students for a better understanding of the unitary evaporation operation.